Early and late basilar artery thrombectomy time window outcomes - Mierzwa, Adam T.; Rao, Rahul; Al Kasab, Sami; Nelson, Ashley; Ortega-Gutierrez, Santiago; Vivanco-Suarez, Juan; Farooqui, Mudassir; Jadhav, Ashutosh P.; Desai, Shashvat; Toth, Gabor; Alrohimi, Anas; Nguyen, Thanh N.; et al. (Frontiers in Neurology, 2024)
Importance: Stroke-to-recanalization time is a strong predictor of outcomes in anterior circulation large vessel occlusion (LVO). We aimed to evaluate functional outcomes in early (<6 hours) vs late (6-24 hours) time windows for thrombectomy-treated basilar artery occlusions. Methods: Patients were derived from the Posterior Circulation Ischemic Stroke Evaluation: Analyzing Radiographic and Intra-procedural Predictors of Mechanical Thrombectomy (PC-SEARCH) Registry and retrospectively analyzed early and late basilar artery thrombectomy time windows cohorts. Patients were dichotomized based on last known well and correlated to 90-day functional outcomes (mRS 0-3). Multiple logistic regression analysis was performed. Results: Four-hundred-five patients were included in this study. There were 216 and 189 patients in the early and late time windows, respectively. Baseline demographic, stroke, radiographic, and intraprocedural characteristics were similar between groups. Ninety-nine (46%) and 79 (42%) patients in the early and late time window, respectively, achieved favorable functional outcome at 90-days (p = 0.41) and multiple logistic regression analysis did not reveal differences between cohorts (OR 0.74 95% CI 0.46 -1.19; p = 0.22). Symptomatic hemorrhage (7% vs 5%; p = 0.69) and neurological complications (8% vs 9%; p= 0.83) were similar between groups; however, hospital complications were more common in the early time window cohort (22% vs 13%; p= 0.01). Conclusion: Early and late thrombectomy time window can achieve similar rates of 90-day favorable functional outcomes. However, timely thrombectomy influences likelihood of achieving excellent functional outcomes (mRS ≤ 2) within the early time window.